Assessment of the Energy Efficiency of Three-Phase Induction Motors Powered by A Photovoltaic System - Charris, Narciso Castro; Santos, Vladimir Sousa; Eras, Juan J. Cabello; Fandiño, Jorge M. Mendoza (International Journal of Energy Economics and Policy, 2024)
This study aims to determine the energy efficiency of three-phase induction motors (TIM) powered when operated with photovoltaic systems (PVS). The environmental advantages of photovoltaic systems (PVS) are very well known. However, there are still challenges related to energy quality, electricity generation instability, failure in frequency regulation, instability in reactive power, and harmonics generation. However, the impact of PVS on TIM efficiency has not been thoroughly explored. This research compares a TIM’s electromechanical characteristics and efficiency when powered by a conventional electrical grid versus a PVS. Experimental studies revealed that when powered by the PVS, the TIM experienced increased voltage and higher voltage and current harmonics compared to grid power. These electrical difficulties, attributed to the PVS inverter, resulted in a 2.7% decrease in TIM efficiency compared to grid power. Modeling conducted under actual load variation conditions demonstrated a 2.6% increase in energy consumption when powered by the PVS compared to grid power. Based on these findings, PVS installers are advised to consider the energy quality provided by these systems, as it may affect the efficient operation of TIM, leading to increased energy consumption.